2015
DOI: 10.1088/0004-637x/799/2/183
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATION BETWEEN STAR FORMATION RATE AND STELLAR MASS FOR GALAXIES AT 3.5 ⩽z⩽ 6.5 IN CANDELS

Abstract: Distant star-forming galaxies show a correlation between their star formation rates (SFR) and stellar masses, and this has deep implications for galaxy formation. Here, we present a study on the evolution of the slope and scatter of the SFR-stellar mass relation for galaxies at 3.5 ≤ z ≤ 6.5 using multiwavelength photometry in GOODS-S from the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) and Spitzer Extended Deep Survey. We describe an updated, Bayesian spectral-energy distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
392
5

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 310 publications
(462 citation statements)
references
References 180 publications
(280 reference statements)
65
392
5
Order By: Relevance
“…Lyα emitting galaxies with redshifts 1.9 < z < 3.6 by Hagen et al (2014) and star-forming galaxies with redshifts z ∼ 3.4 by Troncoso et al (2014) are shown by dark-grey stars and asterisks, respectively. The relations for galaxies with z ∼ 4 by Bouwens et al (2012) and for galaxies with z ∼ 5 -6 by Salmon et al (2015) are indicated by thick solid red and yellow lines, respectively. The galaxy candidates with z ∼ 9 -11 by Coe et al (2013) and Oesch et al (2014) are shown by large open dark-grey triangles.…”
Section: Hβ Luminosity -Stellar Mass Relationmentioning
confidence: 98%
“…Lyα emitting galaxies with redshifts 1.9 < z < 3.6 by Hagen et al (2014) and star-forming galaxies with redshifts z ∼ 3.4 by Troncoso et al (2014) are shown by dark-grey stars and asterisks, respectively. The relations for galaxies with z ∼ 4 by Bouwens et al (2012) and for galaxies with z ∼ 5 -6 by Salmon et al (2015) are indicated by thick solid red and yellow lines, respectively. The galaxy candidates with z ∼ 9 -11 by Coe et al (2013) and Oesch et al (2014) are shown by large open dark-grey triangles.…”
Section: Hβ Luminosity -Stellar Mass Relationmentioning
confidence: 98%
“…Many studies have shown a relatively tight correlation (typical dispersion of ∼0.2 dex) between SFR and stellar mass (main sequence of star-forming galaxies), or equivalently between sSFR and stellar mass out to z∼6 (Brinchmann et al 2004;Daddi et al 2007;Elbaz et al 2007;Noeske et al 2007;Salim et al 2007;Karim et al 2011;Reddy et al 2012;Whitaker et al 2012;Sobral et al 2014;Salmon et al 2015;Shivaei et al 2015a). Since we found that EW [O II] and sSFR [O II] are related, we expect to see a relation between EW [O II] and stellar mass.…”
Section: Line Ewmentioning
confidence: 99%
“…In order to calculate the expected line fluxes for a given BC03 galaxy template, we calculate the integrated Lyman continuum flux (before dust attenuation) and use the relation from Leitherer & Heckman (1995) to calculate the expected fluxes from hydrogen recombination lines (mainly Hα, Hβ, Paβ, and Brγ) while assuming the Lyman continuum escape fraction to be zero. Non-zero Lyman continuum escape fraction will reduce the strength of optical nebular emission lines (see Inoue 2011 andSalmon et al 2015). We then use the tabulated line ratios between Hβ and the metal lines from Anders & Alvensleben (2003) to calculate the metal line fluxes for a metallicity of 0.2Z e .…”
Section: Modeling Proceduresmentioning
confidence: 99%